2017
DOI: 10.1111/bjhp.12245
|View full text |Cite
|
Sign up to set email alerts
|

The impact of telephone‐delivered cognitive behaviour therapy and befriending on mood disorders in people with chronic obstructive pulmonary disease: A randomized controlled trial

Abstract: Cognitive behaviour therapy reduced depression symptoms but not anxiety. Befriending reduced depression symptoms in the short term and anxiety symptoms in both the short term and long term. Further research is needed to demonstrate non-inferiority of telephone delivery compared with other formats, and to understand the impact of befriending which has the potential to be a cost-effective support for people with COPD. Statement of contribution What is already known on this subject? Depression and anxiety are com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 40 publications
(67 reference statements)
1
42
1
Order By: Relevance
“…It is an effective treatment for anxiety, depressive symptoms and physical health. Methods of dysfunction, there is evidence that it is effective for patients with COPD combined with anxiety and depression [12,13]. Relevant evidence suggests that CBT is as effective as medication and may be the first choice for patients with mental health problems [14,15].…”
mentioning
confidence: 99%
“…It is an effective treatment for anxiety, depressive symptoms and physical health. Methods of dysfunction, there is evidence that it is effective for patients with COPD combined with anxiety and depression [12,13]. Relevant evidence suggests that CBT is as effective as medication and may be the first choice for patients with mental health problems [14,15].…”
mentioning
confidence: 99%
“…The use of CBT has gained traction because of its effectiveness in achieving symptomatic relief for patients with chronic illnesses (100,168). In the COPD population, there have been numerous studies of varying quality and sample size that have shown promising results (37,(169)(170)(171)(172)(173)(174)(175)(176) Cost-effectiveness is undoubtedly an important issue, particularly given tightening health budgets, and increasing service imperatives to reduce health care spending. One study has shown that face-to-face CBT is effective and also may be cost-neutral when implemented in COPD patients (168).…”
Section: Relaxation Therapymentioning
confidence: 99%
“…The use of telephone-based interventions for depression has shown to be just as effective as face-to-face (177)(178)(179), has shown to be beneficial for patients with anxiety and depression associated with other chronic diseases (180,181) and to be costsaving among patients with COPD (182). A recent study evaluating the role of telephone-based CBT treatment for anxiety and depression for patients with COPD showed a significant reduction in depression but not anxiety symptoms (37).…”
Section: Relaxation Therapymentioning
confidence: 99%
See 2 more Smart Citations